2006
DOI: 10.1007/s10874-006-9056-4
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory measurements of the 12C/13C kinetic isotope effects in the gas-phase reactions of unsaturated hydrocarbons with Cl atoms at 298 ± 3 K

Abstract: Abstract. The carbon kinetic isotope effects (KIEs) in the reactions of several unsaturated hydrocarbons with chlorine atoms were measured at room temperature and ambient pressure using gas chromatography combustion isotope ratio mass spectrometry (GCC-IRMS). All measured KIEs, defined as the ratio of the rate constants for the unlabeled and labeled hydrocarbon reaction k 12 /k 13 , are greater than unity or normal KIEs.The KIEs, reported in per mil according to Cl ε = (k 12 /k 13 -1) × 1000‰ with the number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Thus measurement of the stable carbon isotope ratios of saturated NMHC is less promising for the elucidation of tropospheric Cl atom chemistry than isotope ratio studies for unsaturated hydrocarbons. 49 For the interpretation of tropospheric measurements of the stable carbon isotope ratios of NMHC, the most important consequence of our findings is that, in general, reactions with Cl atoms will have a very limited impact on the measured isotope ratio. Possible exceptions are conditions with a dominating influence of Cl atom chemistry such as ozone depletion episodes in the boundary layer during polar sunrise.…”
Section: Discussionmentioning
confidence: 78%
“…Thus measurement of the stable carbon isotope ratios of saturated NMHC is less promising for the elucidation of tropospheric Cl atom chemistry than isotope ratio studies for unsaturated hydrocarbons. 49 For the interpretation of tropospheric measurements of the stable carbon isotope ratios of NMHC, the most important consequence of our findings is that, in general, reactions with Cl atoms will have a very limited impact on the measured isotope ratio. Possible exceptions are conditions with a dominating influence of Cl atom chemistry such as ozone depletion episodes in the boundary layer during polar sunrise.…”
Section: Discussionmentioning
confidence: 78%
“…Except for one rate coefficient measurement for the reaction with cyclopentene [18], there are no previous rate coefficient data, at least to our knowledge, for the reactions of chlorine atoms with cycloalkenes. Even in the case of cyclopentene, the reported value (Table II) is at least two times higher than the presently measured rate coefficient.…”
Section: Discussionmentioning
confidence: 97%
“…[17]. However, there are not many studies on the rate coefficients, or mechanism of reactions of Cl atoms with these cyclic alkenes, except for a measurement of Cl atom reactions with cyclopentene by Anderson et al [18]. In the present study, the rate coefficients of reactions of Cl atoms with three cyclic alkenes, cyclopentene, cyclohexene, and cycloheptene, are determined using the relative rate method, to assess the significance of these reactions in the troposphere.…”
Section: Introductionmentioning
confidence: 95%
“…At room temperature, the total rate coefficient for the Cl atom reaction with p -cymene is found to be 2 times larger than the ones measured for o -, m -, and p -xylene and 3 times larger than the one measured for toluene. Wallington et al, Shi and Bernhard, and Anderson et al reported the rate coefficients for the Cl atom reaction with o -, m -, and p -xylene which fall in the range (1.2–1.5) × 10 –10 cm 3 molecule –1 s –1 . The reported values for the Cl atom reaction with toluene at room temperature fall in between 5.6 and 6.1 × 10 –11 cm 3 molecule –1 s –1 . ,, The experimental results on the reaction products and isotope effects indicate that the reactions of Cl atom with alkyl aromatics like toluene, xylene, alkyl naphthalenes, etc., proceed via an abstraction reaction, whereas we have calculated the rate coefficients of the p -cymene + Cl reaction only for addition channels.…”
Section: Resultsmentioning
confidence: 99%
“…At room temperature, the total rate coefficient for the Cl atom reaction with p-cymene is found to be 2 times larger than the ones measured for o-, m-, and p-xylene and 3 times larger than the one measured for toluene. Wallington et al, 57 Shi and Bernhard, 58 and Anderson et al 59 reported the rate coefficients for the Cl atom reaction with o-, m-, and p-xylene which fall in the range (1.2−1.5) × 10 −10 cm 3 molecule −1 s −1 . The reported values for the Cl atom reaction with toluene at room temperature fall in between 5.6 and 6.1 × 10 −11 cm 3 molecule −1 s −1 .…”
Section: Rate Coefficientsmentioning
confidence: 99%